a Isolasi dari Ekstrak Daun Pandan (Pandanus amaryllifolius) Sebagai Anti Bakteri: Systematic Literatur Review: SLR: Isolasi ekstrak daun pandan sebagai anti bakteri - Wiji Utami; Nuliyana Harnita (JSSIT: Jurnal Sains dan Sains Terapan, 2025)
Pandan leaves are known as an herbal medicinal plant and are widely used for various diseases. The bioactive compound of pandan leaves has been exhibited to have pharmacological activity as an anti-bacterial. This SLR research aimed to determine the method and type of solvent used to isolate secondary metabolite from pandan leaves. The method used in this research is the PRISMA 2020 using the Publish or Perish application. Articles were obtained from Google Scholar. The evaluation results in this study found that 28 manuscripts fulfil the criteria for isolating natural compounds. Based on the SLR results, it was discovered that the disc diffusion method was frequently employed in this research in ten articles due to its high sensitivity, ease of extraction, and low cost. Meanwhile, ethanol is the most commonly employed solvent in this research because it is inexpensive, low in toxicity, and soluble in water and fat. This study's findings can be utilized to help researchers conduct isolation on natural materials.